Alternative Dispute Resolution and the Rule of Law in International Development Cooperation - Michel, James (World Bank, Washington, DC, 2014)
The role of alternative dispute resolution (ADR) in efforts to strengthen the rule of law is attracting increased interest in international development cooperation. From a development perspective, the principal interest in this question is a concern for expanding rights and opportunities for poor people who do not fully benefit from the protection of the law in their daily lives. Other interests in ADR, such as in commercial arbitration and court-annexed mediation in civil litigation, also have important positive implications for development. Facilitating commerce and expediting the disposition of lawsuits are valuable services and worthwhile undertakings. However, the principal focus for development is on the non-formal processes intended to expand access to justice. These include statutory schemes, such as the barangay justice system in the Philippines; state-sponsored mediation centers, such as those of the Procurador General in El Salvador; traditional systems that provide the vast majority of dispute-resolution services in many African countries; and systems of mediation and conciliation operated by public and private entities throughout the world. This paper briefly reviews the concept of development and related international cooperation. It then examines how the rule of law has been addressed in development programs and offers some thoughts about the contribution of ADR for advancing the rule of law and, in turn, contributing to human security, well being, and dignity.